Vaccine Protection Through Placenta and Breastfeeding: The Unmet Topic in COVID-19 Pandemic - Laguila Altoé, Ariane; Marques Mambriz, Anna Paula; Cardozo, Daniela Maira; Valentini Zacarias, Joana Maira; Laguila Visentainer, Jeane Eliete; Bahls-Pinto, Larissa Danielle (Frontiers in Immunology, 2022)
The COVID-19 pandemic turns pregnant women's health care a worldwide public health challenge. Although initial data did not demonstrate pregnancy as a more susceptible period to severe outcomes of acute SARS-CoV-2 infection, there is an increasing number of reports showing that not only pregnant women might be at significantly higher risk than non-pregnant women by COVID-19, but also the fetus. These findings may be related to adaptive changes that occur during pregnancy, such as the reduction in the residual respiratory capacity, the decrease in viral immune responses, and the increased risk for thromboembolic events. Additionally, despite the SARS-CoV-2 vertical transmission evidence is uncommon, the maternal illness severity might reflect serious perinatal and neonatal outcomes. Thus, protecting the maternal-fetal dyad against COVID-19 is critical. Even though pregnant women initially were excluded from vaccine trials, several studies have provided safety and efficacy of the overall vaccine COVID-19 platforms. Vaccination during pregnancy becomes a priority and can generate benefits both for the mother and newborn: maternal neutralizing antibodies are transmitted through placenta and breastfeeding. Moreover, regarding passive immunization, human milk contains other bioactive molecules and cells able to modulate the newborn’s immune response, which can be amplified after the vaccine. Nonetheless, many issues remain to be elucidated, considering the magnitude of the protective immunity transferred, the duration of the induced immunity, and optimal interval for pregnant immunization. In this review, we assessed these unmet topics supported by literature evidence regarding the vaccine's immunogenicity, pregnancy immune heterogeneity, and the unique human milk antiviral features.